The mechanistic role of chemically diverse metal ions in the induction of autophagy. (May 2017) - Sahni, Sumit; Bae, Dong-Hun; Jansson, Patric J.; Richardson, Des R.
Graphical abstract: Abstract: Autophagy is an evolutionary conserved cellular catabolic degradation process in response to stress which involves lysosomal degradation of unnecessary or damaged organelles and misfolded proteins. This is primarily a pro-survival pathway providing the cell with essential nutrients during stressful conditions. There are number of essential metal ions, which are required for normal physiological functioning of cells. Studies have shown that autophagy can be regulated by cellular metal ion concentrations. On the other hand, autophagy is also shown to regulate intracellular levels of certain metal ions. This review discusses recent advances in the research examining the role of metal ions in the autophagic pathway.